Contributions of Neuroscience to Educational Praxis: A Systematic Review - Evgenia Gkintoni; Ioannis Dimakos; Constantinos Halkiopoulos; Hera Antonopoulou (Emerging Science Journal, 2023)
Objectives: In education, neuroscience is an interdisciplinary research field. It seeks to improve educational practice by applying brain research findings. Additional findings from the scientific fields of education, psychology, and neurophysiology aim to enhance the learning process and improve educational practices. The application of neuroscience to education involves neuroscientific and psychological knowledge. Methods/Analysis: In this systematic literature review, the final studies included in the analysis table are decided by searching databases according to predefined inclusion criteria. The PRISMA approach was utilized to study the relationship between neuroscience and the educational process and to optimize the educational process based on the relevant data. Findings: The review's findings emphasize the significance of integrating neuroscience into educational praxis and challenges and raise ethical concerns regarding its implementation in educational contexts. Novelty /Improvement: The discipline of educational neuroscience is associated with education, research, and the cognitive neuroscience of learning. Neuroscience can serve as the basis for education in a similar direction that biology serves as the basis for medicine, meaning that each field retains its innovation but cannot contravene the rules of the other. This study examines the relationship between neuroscience and educational praxis as well as how the educational community might bridge this gap to include prospective findings from neuroscientific research. Doi: 10.28991/ESJ-2023-SIED2-012 Full Text: PDF